Konsep al-Huzn Para Nabi Menurut Psikospiritual Islam: Concept of al-Huzn of the Prophets according to Islamic Psychospiritual - Syed Muhsin, Sharifah Basirah; Rajab, Khairunnas; Zainalabidin, Murshidatun Nur (Jurnal Usuluddin, 2024)
The al-Huzn, which translates to sadness and is sometimes classified as depression by Islamic psychologists, is an emotion experienced by individuals when confronted with difficulties, often leading to a sense of deep sadness. These feelings are considered normal human responses to challenging or heartbreaking events. There is a question among some whether prophets also experienced sadness. This confusion stems from the perception that prophets, due to their elevated spiritual status and closeness to Allah SWT, may not experience sadness. This article aims to explore the concept of al-Huzn among prophets according to Psychospiritual Islam, and to illustrate the Islamic Psychospiritual elements through which prophets addressed and coped with al-Huzn. Article indicates that prophets did indeed experience al-Huzn, as interpreted by scholars based on Quranic verses relating to prophets' emotional states. The article also identifies factors that led to al-Huzn among prophets, as well as the effects resulting from these emotions. Furthermore, Islamic Psychospiritual elements are discussed as solutions utilized by prophets in facing al-Huzn. These elements provide a framework for understanding how prophets navigated their emotional challenges within an Islamic context.